BCG vaccine: a hope to control COVID-19 pandemic amid crisis - Yashpal Singh Malik; Mohd Ikram Ansari; Balasubramanian Ganesh; Shubhankar Sircar; Sudipta Bhat; Tripti Pande; OR Vinodhkumar; Prashant Kumar; Mohd Iqbal Yatoo; Ruchi Tiwari; Nadia Touil; Shailesh Kumar Patel; et al. (Taylor & Francis Group, 2020)
COVID-19 caused by the virus SARS-CoV-2 has gripped essentially all countries in the world, and has infected millions and killed hundreds of thousands of people. Several innovative approaches are in development to restrain the spread of SARS-CoV-2. In particular, BCG, a vaccine against tuberculosis (TB), is being considered as an alternative therapeutic modality. BCG vaccine is known to induce both humoral and adaptive immunities, thereby activating both nonspecific and cross-reactive immune responses in the host, which combined could effectively resist other pathogens including SARS-CoV-2. Notably, some studies have revealed that SARS-CoV-2 infectivity, case positivity, and mortality rate have been higher in countries that have not adopted BCG vaccination than in countries that have done so. This review presents an overview of the concepts underlying BCG vaccination and its nonspecific immuological effects and protection, resulting in 'trained immunity' and potential utility for resisting COVID-19.